Heat shock protein 90 inhibitor NVP-AUY922 exerts potent activity against adult T-cell leukemia–lymphoma cells - Taniguchi, Hiroaki (Blackwell Publishing Ltd, 2014)
Adult T-cell leukemia–lymphoma (ATL), an aggressive neoplasm etiologically associated with HTLV-1, is a chemoresistant malignancy. Heat shock protein 90 (HSP90) is involved in folding and functions as a chaperone for multiple client proteins, many of which are important in tumorigenesis. In this study, we examined NVP-AUY922 (AUY922), a second generation isoxazole-based non-geldanamycin HSP90 inhibitor, and confirmed its effects on survival of ATL-related cell lines. Analysis using FACS revealed that AUY922 induced cell-cycle arrest and apoptosis; it also inhibited the growth of primary ATL cells, but not of normal PBMCs. AUY922 caused strong upregulation of HSP70, a surrogate marker of HSP90 inhibition, and a dose-dependent decrease in HSP90 client proteins associated with cell survival, proliferation, and cell cycle in the G1 phase, including phospho-Akt, Akt, IKKα, IKKβ, IKKγ, Cdk4, Cdk6, and survivin. Interestingly, AUY922 induced downregulation of the proviral integration site for Moloney murine leukemia virus (PIM) in ATL cells. The PIM family (PIM-1, -2, -3) is made up of oncogenes that encode a serine/threonine protein kinase family. As PIM kinases have multiple functions involved in cell proliferation, survival, differentiation, apoptosis, and tumorigenesis, their downregulation could play an important role in AUY922-induced death of ATL cells. In fact, SGI-1776, a pan-PIM kinase inhibitor, successfully inhibited the growth of primary ATL cells as well as ATL-related cell lines. Our findings suggest that AUY922 is an effective therapeutic agent for ATL, and PIM kinases may be a novel therapeutic target.